Realization of Nth-Order Voltage Transfer Function using Current Conveyors CCII - Cajka, J.; Dostal, T.; Vrba, K. (Radioengineering Society, 1997)
A universal method for the realization of arbitrary voltage transfer function in canonic form is presented. A voltage-controlled current-source using a plus-type second-generation current conveyor is here applied as the basic building element. Filters designed according to this method have a high input impedance and low sensitivity to variations of circuit parameters. All passive elements are grounded.
Keywords: circuit theory; current conveyors; active filters